2014
DOI: 10.1039/c4cp02237h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a detonation nanodiamond coating on the thermal decomposition properties of RDX explosives

Abstract: A well-dispersed and uniformly shaped detonation nanodiamond (DND) was produced and coated over micron scale RDX in various amounts to form four kinds of DND coating composites (NDRs). In order to confirm the optimal coating amount and its effect on the thermal properties, the thermal decomposition and kinetics were studied by DSC, TG and DPTA techniques. The critical temperature of thermal explosion (Tb) and the self accelerating decomposition temperature (T(SADT)) both exhibit an interesting volcano-shaped c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…It is worthy to note that E a signifies the minimum energy level that the colliding molecules must possess in order to undergo a given chemical reaction [38].…”
Section: Calculation Of Isothermal Reaction Kinetics Of Vst Data By Mmentioning
confidence: 99%
“…It is worthy to note that E a signifies the minimum energy level that the colliding molecules must possess in order to undergo a given chemical reaction [38].…”
Section: Calculation Of Isothermal Reaction Kinetics Of Vst Data By Mmentioning
confidence: 99%
“…216 The nDs can also slightly reduce the T p of RDX. 81 In contrast, when a fullerene-based catalyst (mNPF) is added to RDX, its T p drops from 240.4°C to 234.0°C and the corresponding exothermic heat increases from 499.5 to 891.8 J g −1 . There is another fullerene-based catalyst, FED, whose catalytic effect has not yet been studied.…”
Section: Effects Of Cnms On Performances Of Emsmentioning
confidence: 99%
“…It was reported that well-dispersed and uniformly shaped DnDs were produced and used to coat of micron-sized RDX particles. 81 SEM images of these materials are shown in Fig. 5.…”
mentioning
confidence: 99%
“…However, their direct influence on the performance of existing additives has not been extensively studied to date. Since nanodiamonds have been reported to suppress reaction kinetics in certain systems by raising the activation energy for reactions [14], it is critically important to assess their direct effect on the reaction activities of existing anti-wear additives. Prior studies on various reaction mechanism paths through which phosphate esters form films on Fe surfaces have revealed that there is a requirement to overcome an activation energy to break either P-O or O-C bonds on the phosphate esters, depending on whether they are aliphatic or aromatic [15][16][17].…”
mentioning
confidence: 99%